Time to Competency: Reliability of Flexible Transnasal Laryngoscopy by Resident Training Level. (2nd September 2014) - Brook, Christopher; Platt, Michael P.; Cabral, Howard; Russell, Kimberly; Grillone, Gregory A.; Aliphas, Avner; Noordzij, J. P.
Abstract : Objectives: Determine the progression of flexible transnasal laryngoscopy reliability and competency in otolaryngology residency training. Methods: Prospective study of flexible transnasal laryngoscopy interpretations. Seventeen otolaryngology residents from PGY‐1 to PGY‐5 and 3 attending otolaryngologists viewed 25 selected and digitally‐recorded flexible transnasal laryngoscopies. The evaluators were asked to rate 13 items relating to abnormalities in the oropharynx, hypopharynx, larynx, and subglottis. The level of concern and level of comfort with the diagnosis were assessed. Intraclass correlations were calculated for each topic and by level of training to determine reliability within each class, and competency compared to attending interpretations. Results: Intraclass correlation of residents compared with attending physicians demonstrated significant improvements by year for left vocal fold immobility (ICC 0.85‐0.96), right vocal cord immobility (ICC 0.80‐0.97), subglottic stenosis (ICC 0.70‐0.97), and level of concern (ICC 0.72‐0.87). There were no trends for base of tongue abnormalities, pharyngeal abnormalities, pharyngeal masses, and hypopharyngeal masses. For vocal cord immobility, subglottic stenosis, and level of concern, resident reliability was found to be statistically similar to attending physicians in all categories by PGY‐3. Conclusions: Resident competency for flexible transnasal laryngoscopy progresses during residency to reliability with attending otolaryngologists by PGY‐3 over key facets of the examination. Flexible laryngoscopy may be a useful metric for procedural competency assessment during residency training.